Translation method in Indonesian best seller book of David J Schwartz - Luluk Gusliyanah; Unpris Yastanti (LADU: Journal of Languages and Education, 2021)
Background: the method of translation is a way to translate a text based on the purpose of the text or the message which the writer wants to send to the reader. Purpose: This paper aims to identify the translation method which commonly use in The Magic of Thinking Big Book by David J Schwartz. Design and methods: This study uses the descriptive method to analyze this book. The writer finds and get some data and then analyze the data and information by searching internet and library research. Results: This study revealed six translation method in chapter five of The Magic of Thinking Big by David J Schwartz. Those of translation methods are: Literal Translation, Faithful Translation, Adaptation, Free Translation, Idiomatic Translation and Communicative Translation. However, from six methods which the writer finds, there is the most dominant one which the writer finds in that book. It is Free Translation method.